Metabolic reprogramming in melanoma therapy - Dongliang Shen; Lu Zhang; Shun Li; Liling Tang (Cell Death Discovery)
Abstract Melanoma, a deadly and aggressive cancer, exhibits significant metabolic reprogramming that supports energy production, biosynthesis, and tumor progression. This metabolic adaptation drives melanoma growth, proliferation, metastasis, and therapy resistance, highlighting its potential as a promising target for therapeutic intervention. This review focuses on the latest studies elucidating metabolic pathways involved in melanoma progression, therapeutic response, and resistance. Additionally, the potential of targeting metabolic pathways–either alone or in combination with established therapeutic inhibitors–to block disease progression in melanoma is also discussed. Such insights might improve our understanding of metabolic pathways in melanoma development and foster advancements in melanoma therapy.